Phytochemical Studies on Parthenium hysterophorus Linn. - SANTHI, P.R.; ANBUSRINIVASAN, P. (Asian Journal of Chemistry, 2010)
Various fractions obtained from Parthenium hysterophorus contains antiinflammatory activities . The fraction obtained from diethyl ether was found to be a flavonol galangin. Aglycone and glucose fractions were also obtained during fractionation. All the fractions were characterized by UV-spectral analysis. The ethyl acetate fraction obtained was analyzed for its microbial activity, which showed a dose-dependent activity against heamolysis.